In the shadow of war… Culture and free time of the military and civilian population in Lublin during the Austro-Hungarian occupation (1915–1918) - Jakimowicz, Anna (City and War, 2021)
In the fall of 1915, Lublin became the capital of the General Military Governorate, which resulted in an influx of military and civilians from C.K. Monarchy and Galicia. Free time from work was filled with visits to theaters, cinemas, as well as restaurants and confectioneries, which resulted in the flourishing of the cultural sphere, and also the catering, hotel and service industries. Local entrepreneurs, wanting to gain the favor of the occupation authorities, tried to meet their needs and expectations, which was not easy in the face of requisitioning goods, high prices and speculation, and difficult communication. Nevertheless, during the entire period of the occupation, new forms and places of entertainment appeared, the purpose of which was to entertain and temporarily forget from everyday worries. They were used by both officers and civilians, but at that time also two posts were created for military personnel.